Beiträge zur Insektenfauna der DDR: Coleoptera - Haliplidae. - Fichtner, Edgar (Contributions to Entomology = Beiträge zur Entomologie, 1981)
The revision of all the available material established 19 species of the family Haliplidae in the GDR. Data about their frequency and seasonal occurrence and their biology are given.